Pedagogical Effectiveness Of Using Innovative Digital Tools In Higher Education Institutions - Tengelbaeva, Dinora Muratovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the pedagogical effectiveness of using digital platforms and modern software in higher education institutions. It highlights the possibilities of organizing the educational process through digital technologies, increasing student engagement, strengthening knowledge acquisition, and creating individualized learning trajectories. In addition, the advantages and challenges of the digital learning environment are substantiated from a scientific perspective.